2019
DOI: 10.3390/su11226298
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Urbanization and the Eco-Environment: A Case Study of Beijing

Abstract: Beijing is one of the most developed cities in China and has experienced a series of environmental problems. In accordance with the Major Function Zone planning, Beijing is divided into four zones in an attempt to coordinate development between urban areas and the eco-environment. Classic coupling model uses statistical data to evaluate the interactions of these two subsystems; however, it lacks the capability to express dynamic changes to land cover. Thus, we extracted land cover data from Landsat images and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
1
22
0
1
Order By: Relevance
“…Nanjing lies in a subtropical monsoon-climate area with large interannual variation in rainfall, which induces marked fluctuations in the WE state subsystem index. Similar findings have been reported in Beijing, Suzhou, and other cities in eastern China (Huang et al 2019 ; Ji and Ni 2018 ). The annual rainfall in 1992 was only 885.2 mm, and industrial water consumption (Y14) reached the peak, which resulted in that year being the one with the greatest pressure on the WE.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nanjing lies in a subtropical monsoon-climate area with large interannual variation in rainfall, which induces marked fluctuations in the WE state subsystem index. Similar findings have been reported in Beijing, Suzhou, and other cities in eastern China (Huang et al 2019 ; Ji and Ni 2018 ). The annual rainfall in 1992 was only 885.2 mm, and industrial water consumption (Y14) reached the peak, which resulted in that year being the one with the greatest pressure on the WE.…”
Section: Discussionsupporting
confidence: 88%
“…To better explain the degree of mutual coupling and coordinated development of urbanization and WE on the basis of comprehensive research classification, the coupling coordination degree can be divided into three primary development stages, which can be further divided into five secondary development stages (He et al 2017 ; Huang et al 2019 ; Liu et al 2018a , b ) (Table 2 ). Furthermore, nine tertiary development stages can be used to describe the coupling relationship between urbanization (f(x)) and WE (g(y)) (Table 2 ).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…(ii) "Technical Criterion for Ecosystem Status Evaluation" promulgated in 2015 by the former Ministry of Environmental Protection of the People's Republic of China [47], which stipulates the index systems for evaluation on the ecological environment and calculation methods of the indicators, such as E1, E2, E3, E5, E6, E10 and E11. (iii) On the basis of literature review and analysis [4][5][6]20,23,25,29,[31][32][33], indicators adopted by high frequency are selected, such as U1, U3, U4, U5, U6, U7, U10, E8 and E9. (iv) The aspects are related to national economy and people's livelihood [2,[35][36][37][38], such as U6, U7, U8, U9 and U10.…”
Section: Establishment Of Index Systemmentioning
confidence: 99%
“…Per capita disposable income of urban residents (Yuan) (U9) [4,5,32,46] Total retail sales of social consumer goods per capita (Yuan) (U10) [4,23,29,32,46] Number of beds per 10,000 people (Bed) (U11) [6,23,46] Ecological environment…”
Section: Establishment Of Index Systemmentioning
confidence: 99%
“…Taking Beijing as their research object, Huang et al found that, before 2011, Beijing's urbanization level and eco-environment level presented a growing trend, and both were "superiorly balanced". However, since 2011, Beijing's eco-environment has been deteriorating [27].…”
Section: Introductionmentioning
confidence: 99%